Utilização do laser de baixa intensidade (660nm) na hipertensão arterial: uma nova abordagem no tratamento - Conceição Filho, Júlio César (2019)
According to data from the World Health Organization (WHO), cardiovascular diseases are the main cause of death worldwide, approximately 17 million people or one third of all annual deaths. Of these deaths caused by cardiovascular diseases, approximately 9.4 million are caused by arterial hypertension. In order to reduce these numbers and improve the quality of life and longevity of the population, several treatments have been developed, and in most cases the main treatment indicated is pharmacological. Therapies involving the use of specific types of light have been used since mid-1971, with low intensity laser being one of the main sources of light for these treatments, widely used in dentistry and medicine for various treatments such as psoriasis, acne, ulcers, wounds, etc. Many studies have shown that photobiomodulation therapy (PBM) is able to induce vascular smooth muscle (MLV) relaxation independently of the endothelium. This study evaluated the effect of chronic treatment with PBM in hypertensive animals, induced by obesity. It was possible to verify that over six weeks of treatment, PBM was able to reduce blood pressure by values close to baseline.